The role of the principal as school leader in maintaining academic standards in the schooling of at-risk learners: a case study at a school in the northern areas of Port Elizabeth - Draai, Karen Ann (Rhodes University, Faculty of Education, Department of Education, 2011)
Many disadvantaged schools in South Africa are characterised by poor performance, which is often linked to the legacy of the apartheid regime. Yet, some disadvantaged schools are surviving and even producing excellent results. Many successful businessmen, politicians and academics can attest to the success of these schools, being a product of such schools. Leadership, which has received a lot of attention in recent years, are often the cause of schools failing to produce the expected results. Previous studies have shown that leadership is the key to academic excellence and that to lead disadvantaged schools to success requires strong leaders with moral purpose, who possess qualities of transformational leaders, but also leaders who can focus on instructional leadership practices. This study focuses on the role of leadership in maintaining academic standards at a school in the northern areas of Port Elizabeth. The school has a proud tradition of good academic performances and has even been labelled as a 'model C school in the northern areas'. It has been found that teachers are committed and hardworking and the principal is perceived as having expecting high expectations for the children of the area. He believes as an educator one should never give up on the children. The study found that the principal is a strong leader who shows characteristics of a transformational leader and has the drive of an instructional leader to lead the school and to maintain academic standards. He is a well-respected leader who leads with moral purpose and who has the desire to uplift the community. The study has the potential to provide guidance and encouragement to school principals, and to inform the Department of Education's leadership training programmes.
Keywords: School management and organization -- South Africa -- Port Elizabeth; School principals -- South Africa -- Port Elizabeth; Educational leadership -- South Africa -- Port Elizabeth; School discipline -- South Africa -- Port Elizabeth; Children with social disabilities -- South Africa -- Port Elizabeth; Academic achievement -- South Africa -- Port Elizabeth